Using Psychoeducation and Role Induction to Improve Completion Rates in Cognitive Behavioural Therapy. Issue 2 (23rd February 2017) - Delgadillo, Jaime; Groom, Martin
Abstract : Background : Pre-treatment role induction interventions have been suggested to potentially enhance attendance and clinical outcomes in psychotherapy.Aims : This study aimed to evaluate the effects of a programme of three transdiagnostic seminars (TDS) for patients with common mental disorders accessing cognitive behavioural therapy (CBT) in primary care. TDS included CBT psychoeducation and role induction.Method : A random sample of patients ( n = 49) participated in TDS followed by CBT (TDS+CBT) and they were compared with matched controls ( n = 49) accessing usual CBT. TDS participants rated the relevance and quality of this intervention using an acceptability questionnaire (AQ). Treatment completion ( vs dropout) rates were compared across groups using chi-square tests. Post-treatment changes in depression (PHQ-9) and anxiety (GAD-7) symptoms were compared between groups using analysis of covariance controlling for potential confounders. Analyses were based on intention-to-treat principles.Results : Mean AQ ratings of the TDS intervention were comparable across diagnostic groups ( p = .05). Treatment completion rates were significantly higher ( p = .02) in the TDS+CBT group (87.8%) by comparison with usual CBT (68.8%). However, no significant differences in post-treatment symptom changes were found for depression ( p = .34) or anxiety measures ( p = .71).Conclusions : Incorporating a psychoeducational role induction prior to CBT significantly improved treatment retention, but not overall symptom reductions.